10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Simulation and room of errors (ROE)-based education have emerged as effective strategies to enhance medication safety competency among nursing students. This study developed and evaluated an ROE-based education program for preclinical nursing students. Method A nonequivalent control group pretest-posttest design was used. Preclinical nursing students were assigned to either an ROE-based education group or a traditional education group. The program consisted of three progressive stages addressing error prevention, medication context understanding, and high-risk error management. Outcomes included medication error recognition, medication safety knowledge, medication administration confidence, and learning satisfaction. Results The experimental group showed significantly greater improvements in medication error recognition (F = 11.16, p = .001), medication safety knowledge (F = 8.83, p = .003), medication administration confidence (F = 11.32, p = .001), and learning satisfaction (t = -2.53, p = .012) than the control group. Conclusion The leveled ROE-based program appears to be an effective preclinical medication safety education model that can improve short-term medication safety-related competencies.